Do we AGREE on the targets of antihypertensive drug treatment in older adults: a systematic review of guidelines on primary prevention of cardiovascular diseases. (26th October 2021) - Bogaerts, Jonathan M K; von Ballmoos, Leonie M; Achterberg, Wilco P; Gussekloo, Jacobijn; Streit, Sven; van der Ploeg, Milly A; Drewes, Yvonne M; Poortvliet, Rosalinde K E
Abstract: Background: translation of the available evidence concerning primary cardiovascular prevention into clinical guidance for the heterogeneous population of older adults is challenging. With this review, we aimed to give an overview of the thresholds and targets of antihypertensive drug therapy for older adults in currently used guidelines on primary cardiovascular prevention. Secondly, we evaluated the relationship between the advised targets and guideline characteristics, including guideline quality. Methods: we systematically searched PubMed, Embase, Emcare and five guideline databases. We selected guidelines with (i) numerical thresholds for the initiation or target values of antihypertensive drug therapy in context of primary prevention (January 2008–July 2020) and (ii) specific advice concerning antihypertensive drug therapy in older adults. We extracted the recommendations and appraised the quality of included guidelines with the AGREE II instrument. Results: thirty-four guidelines provided recommendations concerning antihypertensive drug therapy in older adults. Twenty advised a higher target of systolic blood pressure (SBP) for octogenarians in comparison with the general population and three advised a lower target. Over half of the guidelines ( n  = 18) recommended to target a SBP <150 mmHg in the oldest old, while four endorsed targets of SBP lower than 130 or 120 mmHg. Although many guidelines acknowledged frailty, only three gave specific thresholds and targets. Guideline characteristics, including methodological quality, were not related with the recommended targets. Conclusion: the ongoing debate concerning targets of antihypertensive treatment in older adults, is reflected in an inconsistency of recommendations across guidelines. Recommended targets are largely set on chronological rather than biological age.